2012
DOI: 10.1158/1535-7163.mct-11-0990
|View full text |Cite
|
Sign up to set email alerts
|

REST Is a Novel Prognostic Factor and Therapeutic Target for Medulloblastoma

Abstract: Medulloblastoma is a malignant pediatric brain tumor. Current treatment following patient stratification into standard and high-risk groups using clinical features, has improved survival. However, a subset of patients with standard-risk features have unanticipated aggressive disease, underscoring the need for a better understanding of tumor biology and development of novel treatments. Poor differentiation, a hallmark of medulloblastomas is associated with elevated expression levels of the repressor of neuronal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
70
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 49 publications
(81 reference statements)
1
70
1
Order By: Relevance
“…Utilization of HDACIs to protect dopamine neurons against the stresses of MPTP and lipopolysaccharide (LPS) has also been determined (Gardian et al, 2004, Chen et al, 2007, Wu et al, 2008, Faraco et al, 2009, Kidd and Schneider, 2011 Recently, it has been reported that elevated expression levels of NRSF are associated with the poor differentiation of medulloblastoma, a specific form of malignant pediatric brain tumors (Taylor et al, 2012). were mounted on glass slides and air dried.…”
Section: Discussionmentioning
confidence: 99%
“…Utilization of HDACIs to protect dopamine neurons against the stresses of MPTP and lipopolysaccharide (LPS) has also been determined (Gardian et al, 2004, Chen et al, 2007, Wu et al, 2008, Faraco et al, 2009, Kidd and Schneider, 2011 Recently, it has been reported that elevated expression levels of NRSF are associated with the poor differentiation of medulloblastoma, a specific form of malignant pediatric brain tumors (Taylor et al, 2012). were mounted on glass slides and air dried.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the epigenetic modification, HDACi are able to upregulate tumor suppressor gene expression, resulting in inhibited cancer cell viability (Gui et al, 2004). For example, several HDACi upregulate the tumor suppressor p53 (Kim et al, 2001) and the repressor element 1-silencing transcription factor (also called neuron-restrictive silencer factor) (Taylor et al, 2012) in cancer cells. These suppressors play important roles in repressing ion channel expression.…”
Section: Discussionmentioning
confidence: 99%
“…18,[29][30][31][32][33][34][35][36][37][38][39][40] Recently, mutations in REST have been shown to predispose to Wilms tumor (MIM: 616806). 41 The identified REST mutations in individuals with Wilms tumor were clustered within the zinc-finger DNA-binding domain of REST ( Figure 2C).…”
mentioning
confidence: 99%